From ‘Humiliation’ to Radical Beliefs: Navigating political subjectivities and ideological shifts in trajectories of radicalization. - Wagner Guilherme Alves da Silva (Vibrant: Virtual Brazilian Anthropology)
Abstract This essay delves into the analysis of the radicalization trajectory of supporters of the Early and Preventive Treatment (TPP), contextualizing it within the Brazilian political and social scenario during the 2023 elections. The focus lies on practices, both discursive and non-discursive, influencing contemporary adherence to far-right ideologies. In particular, the paper highlights how the far-right establishes effective communication with society, exploring Sonia’s central role in becoming an active part of a discursive community. The narrative examines her quest for knowledge, often grounded in fake news and studies without scientific review, related to the TPP. The article explores the dynamics between social inclusion, information-seeking, and the legitimization of identity, emphasizing the importance of situational discomfort in constructing the ethnographic project. The adopted approach highlights local practices as authentic political theories and underscores the need to understand how extreme ideologies are normalized and internalized by social subjects, providing a robust conceptual foundation for analyzing the complexities of radicalization and identity formation in the Brazilian political context.